Test of Acceptance and Protein Levels in Soybean Flour Formulation Muffins as Snacks for Young Women with Chronic Energy Deficiency - Dyah Purbosari Dwi Pitaloka; Juliana Christyaningsih; Annas Buanasita; Erlyna Jayeng Wijayanti (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Chronic energy deficiency in young people is caused by a lack of nutritional intake, such as energy and protein. Consequently, the nutrients required for daily needs are insufficient. This study aims to determine the acceptability test results and protein content in soy flour muffins as a snack for young women with chronic energy deficiency. An experimental study was conducted with 25 participants to assess the acceptability of three muffin formulas, varying in wheat flour to soy flour ratios: 150:0, 90:60, and 80:70. Following processing and acceptability testing, the control and preferred formula were analyzed for protein content in soy flour muffins. The results indicate that the preferred formula among the panelists (DP18) was formula 3, with a wheat flour to soy flour ratio of 80:70, containing a protein content of 10.70%. This formula exhibited an energy density of 4.23 kcal/g and a Protein Energy ratio of 12.31%. Muffins supplemented with 60 g/serving of soy bean can fulfill 10% of daily calorie and protein requirements. Future researchers are encouraged to conduct community-based projects to assess the utility of these muffins in increasing body weight and average arm circumference.